PHYSIOLOGICAL, GROWTH AND YIELD RESPONSE OF POTATO (Solanum tuberosum L.) TO HEAT STRESS - Muhie, Seid Hussen (Potato Journal, 2022)
Climate change adversely affects crop production as the associated rising temperatures damage its physiology and overall yield. Heat stress affects potato at various stages of growth, but sprout development and tuber initiation are the most sensitive to high temperatures. It also affects the photosynthesis (especially PII) activity, thereby limiting the production and partitioning of assimilates to the sink (tuber). The night temperature is more critical for potato tuber initiation and development. Tuber induction is best at 15°C, initiation at 22°C, and setting at 15°C. Yields are expected to decline by 18–32% in the 2050s due to the effects of global warming on potato cultivation. In addition, heat stress impacts quality resulting in physiological disorders. It also impairs the nutritive quality by boosting glycoalkoid levels in tubers, making the tuber bitter to consume. Therefore, strategies must be developed to combat the impact of heat stress. Priority strategic areas include the production of heat-tolerant potato genotypes by genetic engineering techniques such as screening, selection, and breeding as well as exogenous applications of osmoprotectants and agronomic methods.